Use of Communication Technology by Radio Stations in Benue State - Mnguechia, Idye Barbara; Akase, T. M.; Akpede, K. S. (Darul Yasin Al Sys, 2025)
This study investigates the use of communication technologies by radio stations in Benue State, Nigeria, with a focus on identifying the types of technologies commonly employed in broadcasting. Anchored in the Uses and Gratification Theory, the research adopts a survey methodology, utilizing a questionnaire administered to a sample of 151 respondents. The findings reveal that various communication technologies are used by radio stations for functions such as news sourcing, processing, and dissemination. Nearly half of the respondents indicated frequent use of new technologies in these core broadcasting activities. However, the study also shows that the broader adoption of ICT tools remains at an emerging stage, with only 32% of respondents actively using ICTs for a range of purposes, including administrative functions. A key motivation for ICT adoption was the need for timely submission of news reports, acknowledging the time-sensitive and perishable nature of media content. The study concludes that while ICT usage in radio broadcasting is growing, it is not yet fully integrated across operational levels. It recommends greater investment in modern communication technologies, increased government funding, and the recruitment of ICT-savvy professionals to enhance the efficiency and cost-effectiveness of newsgathering and broadcasting processes in Benue State.